Identifying environmental drivers of benthic diatom diversity: the case of Mediterranean mountain ponds - Saúl Blanco; Adriana Olenici; Fernando Ortega; Francisco Jiménez-Gómez; Francisco Guerrero (PeerJ, 2020)
This study aims at elucidating the environmental factors controlling benthic diatom diversity and uniqueness in Mediterranean mountain ponds. Samples of periphytic diatoms were collected in 45 ponds in Andalusia, south of Spain, and analysed by standard methods. Data analysis reveals that diatom diversity is mainly controlled by elevation and hydroperiod. Contrary to the usual findings in the literature, the highest scores on Shannon’s diversity index were found in high-elevation temporary ponds, but this effect is hidden by lake clustering in the analysed dataset. Significant distance-decay similarity (DDS) trends were detected in the analysis of floristic composition among the samples, stressing the importance of spatial factors that may override the effect of other abiotic factors. These findings highlight the role of isolation and dispersal limitation in the configuration of the biogeographical patterns of benthic diatoms.